Determinants of Drinking Water Supply in Indonesia - Angga Yanuar Triesmarandita; Agus Suman; Marlina Ekawaty (AIBPM Publisher, 2022)
The government in carrying out the obligation to provide drinking water, faces the obstacles of the lack of safe and affordable drinking water provision for all communities, as well as the increasing demand for drinking water. Using panel data from 34 provinces in Indonesia during 2016-2019, this study used static panel regression to examine the influence of the supply and demand sides of drinking water on access to improved drinking water source. The results showed that the demand side of drinking water has more influence on access to improved drinking water source, compared to the supply side. This is indicated by the level of education that has a significant influence on access to improved drinking water source, followed by the price of water. The low level of education results in a lack of awareness of the improved use of drinking water source. This result indicates the need for policies from local governments to conduct socialization and education in campaigns for the use of improved drinking water source, especially in areas with low levels of education. In addition, local governments need to set special drinking water rates for the poor people.Keywords: Demand Side, Drinking Water, Panel Data, Public Goods, Supply Side, Universal Access.